Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru di MI NU Raden Rahmat 95 Pasuruan - Mochammad Muat; Rahmat Rahmat (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research uses a qualitative method with a case study approach. Information collection techniques use observation, interviews and documentation. Meanwhile, the data analysis technique uses data collection, reduction and verification. Meanwhile, testing the validity of the data uses triangulation.The research results show that 1) the professional competence of teachers at MI NU Raden Rahmat 95 Pasuruan, all teachers are certified educators.2) Madrasah Head Leadership Strategies in improving teachers' professional competence include carrying out direct supervision and training for teachers, providing role models, creating a sense of togetherness, involving teachers in various training, training, seminars and KKG. 3) Factors inhibiting increasing professional teacher competence include students who are difficult to manage, students who disturb their friends and students who often come in and out of class. K